2020
DOI: 10.2478/otmcj-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture of construction companies in Lagos State, Nigeria

Abstract: AbstractThe study investigated the cultural features of construction companies in Lagos state and determined the organisational culture profile of the construction companies in the study area, with a view to providing information that could enhance the organisational performance of Nigeria construction firms. Primary data were sourced through the administration of 196 structured questionnaires to 98 construction companies (i.e., two questionnaires per company) represented by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…The study's conclusions highlighted the importance of OC and organizational commitment towards the services offered to the general populace. Another study investigated an association between OC, leadership behavior and employee satisfaction among Nigerian nurses (Alao & Aina, 2020). The authors concluded that leaders' symbolic gestures of offering assistance in favor of other employees can augment ties between leaders and co-workers and create a healthy environment, which ultimately improves job efficiency and, in turn, employee satisfaction.…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%
“…The study's conclusions highlighted the importance of OC and organizational commitment towards the services offered to the general populace. Another study investigated an association between OC, leadership behavior and employee satisfaction among Nigerian nurses (Alao & Aina, 2020). The authors concluded that leaders' symbolic gestures of offering assistance in favor of other employees can augment ties between leaders and co-workers and create a healthy environment, which ultimately improves job efficiency and, in turn, employee satisfaction.…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%